Understanding atomic bonding and electronic distributions of a DNA molecule using DFT calculation and BOLS-BC model - Anlin Deng; Hanze Li; Maolin Bo; ZhongKai Huang; Lei Li; Chuang Yao; Fengqin Li (Biochemistry and Biophysics Reports, 2020)
Deoxyribonucleic acid (DNA) is an important molecule that has been extensively researched, mainly due to its structure and function. Herein, we investigated the electronic behavior of the DNA molecule containing 1008 atoms using density functional theory. The bond-charge (BC) model shows the relationship between charge density and atomic strain. Besides, the model mentioned above is combined with the bond-order-length-strength (BOLS) notion to calculate the atomic cohesive energy, the bond energy, and the local bond strain of the DNA chain. Using the BOLS-BC model, we were able to obtain information on the bonding features of the DNA chain and better comprehend the associated properties of electrons in biological systems. Consequently, this report functions as a theoretical reference for the precise regulation of the electrons and the bonding states of biological systems.